Kajian Dinamika Pendidikan - Diskursus Pendidikan Islam dalam Perspektif Pembebasan Hegemoni Kaum Perempuan - Umi Halwati (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Educations are classic problems and increased on dynamics of civilization. Problems of Education become to draw when related to imaging of someone, that is power hegemony, debased woman image, and exaggerated men image. Therefore, study of woman image especially hit unfair of gender, situated behind and woman rights become more important. Go together is situated behind of woman clan, there are some different view and opinion in solution of situated behind and, woman rights, such as: functionalism Structural Stream, Conflict Sociology Stream, Feminism of Marxist, Feminism of Socialism, and Feminism of Theology’s.